PELAKSANAAN PEMBELAJARAN KONSTRUKTIVISTIK DI TK BINTANG HATI DESA SIDETAPA, KECAMATAN BANJAR, KABUPATEN BULELENG - Ni Luh Ika Windayani (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
This study aims to determine constructivist learning in Bintang Hati Kindergarten. Constructivist learning is learning which constructs knowledge, fosters independence and critical thinking skills. This research is a case study research with a qualitative approach. This study involved 23 subjects consisting of 20 children, 2 teachers, 1 headmaster of Bintang Hati Kindergarten. Data collection is done by interview, observation and observation supportive aids. The main instruments are interview guidelines, observation guidelines, and guidelines for observation supportive aids. The data that has been obtained are analyzed using an interactive analysis model. Analysis of the validity of the data is done by triangulation of sources. The results showed: 1) Bintang Hati Kindergarten uses constructivist learning because children can construct their own knowledge to understand an event experienced by a child; 2) Implementation of learning through learning planning that involves children to provide ideas and determine themes. Implementation of learning can improve children's critical thinking skills, children become active and are able to develop concepts which are being studied and use authentic assessment in the evaluation of photos of activities during the learning process. 3) Teachers in Bintang Hati Kindergarten act as facilitators, motivators and the explorer of children's knowledge; and 4) Learning supportive factors, namely, the natural environment supports children to explore, the teacher as a facilitator to provide reciprocal knowledge of children, and use secondhand goods as learning media.Keywords: Constructivist Learning, Qualitative Approach